Which firms are the most innovative? The importance of multinationals and exporters in Portugal - Silva, Armando (2014)
We test the Global Engagement (GE) hypothesis according to which the most globally engaged firms, whether multinationals or exporters, are the most innovative. The test is applied to data from 4815 Portuguese firms for the period 2002–2004 based on the 4th Community Innovation Survey for Portugal. We estimated several Knowledge Production Functions, assuming that knowledge outputs result from the combination of certain knowledge inputs with the flow of ideas coming from the existing stock of knowledge. We found that the more internationally engaged firms create more knowledge output than their domestic counterparts; indeed, the more globalised firms apply more inputs and have the opportunity to use a larger stock of knowledge. Nevertheless, the relative perceived advantage of the more internationally exposed firms is also the result of their globalised nature,and is not directly connected with knowledge inputs or information flows.